Komunikasi Interpersonal antara Laki-Laki dan Perempuan di Tempat Kerja BNPB: Studi tentang Hambatan dan Persepsi Gender - Wisnu Setiawan; Alfadira Yoga Pradana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze interpersonal communication between male and female employees in the Bangkalan Regency National Disaster Management Agency (BNPB) and identify barriers and the influence of gender perceptions on communication effectiveness. The study used a descriptive qualitative approach with in-depth interviews and observation techniques. The results showed differences in communication styles, where male employees tend to be straightforward and task-oriented, while female employees are more persuasive and relational. Communication barriers arise from gender stereotypes, unequal division of labor, and psychological factors. Gender perceptions have been shown to influence the quality of communication and teamwork. This study concludes that although cross-gender interpersonal communication at BNPB is running quite well, strengthening awareness of gender equality and an inclusive work culture is needed to improve the effectiveness of organizational communication.